Isotopic nephrogram . I Hippuran renal Studio 131 and HG Neohydrina . 203 - Bedoya Paredes, Julio (1965)
In December 1961 it was possible to obtain the first corner of renal function with I 131 hippuran in our service and in our country. Connoisseurs of the work conducted and published in 1956 by the group of Taplin and colleagues ( 1, 2 ) and later in 1960 by Nordyke ( 3) and numerous other contemporary publications appeared about was that decided to adapt a computer to perform renal function test with Hippuran 131. In December 1961 , we received as a donation , a team of instruments for measurement of radioisotopes from the Atomic Energy Commission of the United States , through the Atomic Energy Commission of Peru and between instrumental sent and meager that we owned , we had 2 scintillation detectors flat glass an inch in diameter and one-thirty Tracerlab brand ; Averaging two or Ratemeters accounts also Tracerlab an Esterline Angus Enroller curvilinear and rectilinear Texas.